Rapamycin Prevents cyclophosphamide-induced Over-activation of Primordial Follicle pool through PI3K/Akt/mTOR Signaling Pathway in vivo - Linyan Zhou; Yanqiu Xie; Song Li; Yihua Liang; Qi Qiu; Haiyan Lin; Qingxue Zhang (BMC, 2017)
Abstract Background Primordial follicular depletion has thought to be a common adverse effect of chemotherapy especially for female of reproductive age. The study aimed to evaluate the protective effect of rapamycin on the primordial follicles and its potential mechanism for patients receiving chemotherapy. Methods 8-week old BALB/c female mice were randomly assigned into four groups (control; rapamycin; cyclophosphamide; and rapamycin combined with cyclophosphamide). Hematoxylin staining, immunohistochemical, TUNEL, western blotting and ELISA were employed to assess inter-group differences using Student's t-test and Mann-Whitney test. Results Cyclophosphamide depleted the follicular reserve and induced the phosphorylation of the key proteins of PI3K/Akt/mTOR pathway in mice in a dose-dependent manner. Co-treatment with rapamycin significantly reduced primordial follicle loss at all cyclophosphamide dose groups and prevent the follicle growth wave caused by cyclophosphamide treatment (P < 0.05). TUNEL staining showed that no apoptosis occured in the primordial follicles in all groups and fewer apoptosis in large growing follicles were observed in ovaries from rapamycin + cyclophosphamide group compared to that received cyclophosphamide alone. Serum anti-Müllerian hormone (AMH) was significantly reduced in cyclophosphamide alone group, in contrast to the normal level in rapamycin + cyclophosphamide group. Compared to p-Akt/Akt and p-mtor/mtor, p-rps6/rps6 was significantly decreased in rapamycin + cyclophosphamide group (P < 0.05), indicating that rapamycin attenuated the increased level of phosphorylation of rpS6 after cyclophosphamide treatment. Conclusions Rapamycin can prevent the primordial follicle activation induced by cyclophosphamide through PI3K/Akt/mTOR signaling pathway and thus plays a role in preserving the follicle pool. These results suggest that rapamycin may be an effective protection for ovarian function during chemotherapy, which means a new nonsurgical application for protection of ovarian reserve and prevention of POF.